49.3k views
2 votes
If f(x) = 4x + 3 and g(x) = 22 – 3, then f(g(4)) = ???

2 Answers

6 votes

Answer:

f(g(4))=79

Explanation:

given:

f(x) = 4x + 3

g(x) = 22 – 3

g(x) = 19

the x in parentheses represents x's value. if it is just x then example f(x)=3x would be 3x. if f(x) was f(2)=3x, then x would be 2 and f(2)=3x would be 3*2=6

f(g(4))

first solve g(4)

g(x) = 19

g(4)=19 because there are no x

then substitute

f(g(4))

f(19)

f(19) = 4x + 3

all x become 19

f(19) = 4(19) + 3

=76+3

=79

hope this helps.

User Death Metal
by
5.0k points
0 votes
g(4) = 19
f(19) = 79

So f(g(4)) = 79
User Qirohchan
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.